MEKANISME PASAR MODAL ATAU PERDAGANGAN EFEK SYARIAH (FATWA DSN-MUI) - Nurhaeti, Nurhaeti; Nasrulloh, Deka Ahmad (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
In national economic development, the capital market has a strategic role, namely as a source of long-term financing for the business world and an investment vehicle for investors. The problem in the Islamic capital market is that regulations, mechanisms and market transactions as a whole have elements that are prohibited by Islam. Overall, the trading mechanism on the Indonesia Stock Exchange based on the DSN-MUI Fatwa has been well implemented. This can be seen from the indicators of sharia securities issuance criteria, securities trading mechanisms, prohibited types and transactions, and sharia securities. still has a shortcoming, namely the lack of information provided by the broker so that customers get incorrect information such as regarding fees and contracts made more likely to be intended for brokers (companies). Keywords : Mechanism, Sharia Securities Trading, Fatwa DSN-MUI